Why we should remember the Soviet Information Age? - TATARCHENKO, Ksenia (Institutional Knowledge at Singapore Management University, 2022)
How to navigate the rapidly changing digital geopolitics of the world today? How do we make sense of digital transformation and its many social, political, cultural, and environmental implications at different locations around the world?